Linguaggio e bio-politica nel dibattito italiano contemporaneo - Garofalo, Pietro (Rivista Italiana di Filosofia del Linguaggio)
This essay is a contribution to the analysis of the Italian debates in the philosophy of language in the last decades. My starting point will be the current discussions on Italian Theory. This term broadly refers to strands of thinking such as pensiero vivente (Living Thought) of Esposito, pensiero radicale (Radical Thought) or operaismo (Workerism) of Virno and Hardt as well as Agamben’s biopolitcs. In order to explain the Italian difference, the philosopher Roberto Esposito underlines the centrality of notions such as “life”, “history” and “bio-politics” in opposition to “language” and “subject” that are at the core of many traditions of Western Philosophy such as Critical Theory, Analytic Philosophy, Hermeneutics and Deconstruction. Although the debates in Italian Theory are apparently extraneous to the philosophy of language, it would be interesting to examine the role played by the philosophy of language within this paradigm. Hence, I wish to reconsider Esposito’s insights in the light of some reflections about language developed by three Italian philosophers in the last few years: Agamben, Cimatti and Virno. Their philosophical systems allow me to reconstruct a debate characterized by grasping the close relation between language, “the biological layer of life” and “the mobile order of history”.